Prevalence of Pathogenic Gene Mutations and Prognosis Do Not Differ in Isolated Left Ventricular Dysfunction Compared With Dilated Cardiomyopathy. (March 2018) - Hazebroek, Mark R.; Krapels, Ingrid; Verdonschot, Job; van den Wijngaard, Arthur; Vanhoutte, Els; Hoos, Marije; Snijders, Luc; van Montfort, Lieke; Witjens, Maryvonne; Dennert, Robert; Crijns, Harry J.G.M.; Brunner-La Rocca, Hans-Peter; et al.
Abstract : Background: Genetic evaluation is recommended in patients with unexplained dilated cardiomyopathy (DCM), but its diagnostic yield and prognostic relevance in unexplained isolated left ventricular dysfunction (LVdys) is unknown. Methods and Results: A total of 127 LVdys and 262 DCM patients underwent genetic screening. Long-term outcome consisted of a combined end point of life-threatening arrhythmia, heart transplantation, and death. At baseline, LVdys patients were younger and had less frequently New York Heart Association class ≥3 when compared with DCM (55±13 versus 58±12; P =0.019 and 21% versus 36%; P =0.003, respectively). The prevalence of familial disease and pathogenic mutations was similar in LVdys and DCM (45% versus 40%; P =0.37 and 19% versus 17%; P =0.61, respectively). After a follow-up of 56 (31–82) months, outcome did not differ in LVdys compared with DCM patients (hazard ratio, 0.83; 95% confidence interval, 0.47–1.45; P =0.51). Overall, outcome was less favorable in patients with a genetic mutation or familial disease when compared with those without (hazard ratio, 2.7; 95% confidence interval, 1.07–7.7; P =0.048 and hazard ratio, 2.2; 95% confidence interval, 1.2–4.2; P =0.013, respectively). Thus, the diagnostic yield of genetic testing in LVdys and DCM is similarly high. The presence of a gene mutation or familial predisposition results in an equally worse prognosis. Conclusions: Genetic evaluation is advised in LVdys patients and should not merely be restricted to DCM. Abstract : Supplemental Digital Content is available in the text.